Comparative efficacy of some entomopathogenic fungi as biological control of Bemisia tabaci (Hemiptera: Aleyrodidae) in north-east arid zone of Nigeria. - Gadzama, U. N.; Anaso, C. E.; Zakariya, D.; Mailafiya, D. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Four strains of entomopathogenic fungi Beauveria bassiana, Metarhizium anisopliae, Paecilomyces sp and Nomuraea rileyi were evaluated for pathogenicity against Bemisia tabaci in the laboratory invitro using four concentrations of conidia/ml.Thirty whiteflies were used for each set of experiment for each strain of entomopathogenic fungi. They were divided into six groups out of which one group is a control. Each treatment was replicated five times on monthly bases for each concentration along with control. Bemisia tabaci mortality was recorded at two days interval for ten days. Mortality data were analyzed using the Two-Way Analysis of Variance and significant means were differentiated by Duncan Multiple Range Test (DMRT). Compared with the control group, all strains had a significantly increased mortality rate of Whitefly (P < 0.05). The most effective strain was B. bassiana in all the concentrations (mortality range between 81.6±0.01 – 95.2±0.44 % at 10 days post treatment (DPT) followed by N. rileyi (63.6±0.41 - 78.2±0.18) %, least performance was noticed in P. species (42.6±0.01 - 68.2±0.44 %). This study has shown that the potential of entomopathogenic fungi especially B. bassiana and N. rileyi has raised a hope to be harnessed as alternative control measure of Bemisia tabaci at larval stage with further research.